Analysis on Satisfaction Level of Broiler Chicken Farmer in Implementing Business Partnership in South Sulawesi: A Case Study in Maros Regency - . Palmarudi; K. Kasim (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2012)
Broiler farm is one type of business that attracts many farmers in South Sulawesi and one of the driving forces is the presence of nucleus plasma business partnership pattern. Increasing number of companies involved in partnership causing tougher competition among nucleus firms to get the farmer partners. Those who are able to provide the best quality of service will get a lot of farmer partners and will be able to maintain continuity of implementation partnerships. This research aim was to analyze attributes of service quality dimension (reliability, responsiveness, assurance, empathy, tangible) that can give satisfaction to the broiler farmers on the implementation the partnership. Fifty eight broiler farmers, who have implemented partnership, were selected as the sample based on stratified random sampling methods which were distributed proportionally in the long time of partnership period which was 1-5 years, 6-10 years, and more than 11 year. Then, the respondents from each stratum were randomly chosen. In addition, descriptive analysis and Importance-Performance Analysis (IPA) were used to analyze of the data. The results of this study indicated that the level of satisfaction of broiler farmers on implementing the partnership including the classification was quite good. This was reflected by the result of performance analysis between compatibility and interests of farmers which gave a value of 77.04% of the 19 attributes of service quality dimensions of firm nucleus analyzed. There were seven attributes that have high level of interests but the performance was still considered low by the broiler farmer plasma. Therefore, it is suggested to the nucleus firms to improve the attributes and to the plasma broiler farmers to establish their own institutions in order to improve their bargaining position to the firm nucleus.